1997
DOI: 10.1097/00005392-199707000-00040
|View full text |Cite
|
Sign up to set email alerts
|

p53, bcl-2 and Retinoblastoma Proteins as Long-Term Prognostic Markers in Localized Carcinoma of the Prostate

Abstract: p53 and Rb immunohistochemical staining scores were independent predictors of disease specific survival and were superior to conventional pathological prognostic factors of the primary tumor. These findings lay the groundwork for the prospective study of these markers in patients treated with radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 30 publications
2
59
2
2
Order By: Relevance
“…It has been proposed that downregulation of pRB represents an early event in prostate cancer development and loss of pRB is a prognostic marker of cancer progression (Brooks et al, 1995;Theodorescu et al, 1997). Loss of expression of p16, a CDK inhibitor and upstream regulator of pRB, is also of prognostic significance in locally advanced prostate cancer (Chakravarti et al, 2003), with the downregulation of p16 expression probably resulting from gene hypermethylation or gene deletion (Konishi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that downregulation of pRB represents an early event in prostate cancer development and loss of pRB is a prognostic marker of cancer progression (Brooks et al, 1995;Theodorescu et al, 1997). Loss of expression of p16, a CDK inhibitor and upstream regulator of pRB, is also of prognostic significance in locally advanced prostate cancer (Chakravarti et al, 2003), with the downregulation of p16 expression probably resulting from gene hypermethylation or gene deletion (Konishi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation and altered expression of other upstream regulators of pRB such as p53, p21 and MDM2 (Gao et al, 1995;Osman et al, 1999;Leite et al, 2001) have also been observed in prostate cancer, although mutations in the p53 gene are most frequently associated with metastatic and hormone-refractory disease (Heidenberg et al, 1995). It is particularly significant that prostate cancer exhibits both downregulation of pRB (Brooks et al, 1995;Theodorescu et al, 1997) and overexpression of E2F3. In bladder cancer, it appears that E2F3 overexpression and pRB inactivation can occur in the same tumours, and we have proposed that cooperation between these two events is required for bladder carcinogenesis (Feber et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to removal of RB1 itself, many of the genetic changes found in bladder cancer may indirectly lead to pRB inactivity, for example, elevating cyclin D1, removing the cyclin-dependent kinase (CDK) inhibitor p16, mutating the TP53 gene or amplifying and overexpressing MDM2 (Knowles, 2001). For prostate cancer, it has been proposed that downregulation of pRB represents an early event in prostate cancer development and loss of pRB is a prognostic marker for cancer development (Theodorescu et al, 1997). Loss of expression of p16 an upstream regulator of pRB is also of prognostic significance in locally advanced disease (Chakravarti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, abnormal bcl-2 or bax expression was not significantly associated with Gleason Score or stage; although a borderline relationship of bax expression to Gleason Score was observed (Table 3). While some relationships of these biomarkers to Gleason Score have been reported (9,(22)(23)(24), this has not been a consistent finding (25)(26)(27). In a report of patients with Stage B, C, or D disease, Amirghofran et al (28) found that bax, but not bcl-2 expression, was significantly related to prostate carcinoma stage (p = 0.031); no correlation to Gleason Score was observed for either biomarker.…”
Section: Discussionmentioning
confidence: 95%